2022
DOI: 10.29050/harranziraat.1016268
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofertilizers, seaweed extract and inorganic fertilizer on growth and yield of lettuce (Lactuca sativa var. longifolia L.)

Abstract: Biyogübre, deniz yosunu ve inorganik gübrelerin marulda (Lactuca sativa var. longifolia L.) bitki gelişimi ve verimi üzerine etkisi

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Seaweeds increase the quality and performance of plants by containing cytokinins that plants need [32]. Mohammed et al [33], in their study on lettuce, reported that the number of leaves and leaf area decreased depending on the dose increase of SW applications, had no effect on stem diameter and chlorophyll content, however increased head weight and yield. Demir et al [34] observed that SW extracts were effective in seedling growth and accelerated growth.…”
Section: Discussionmentioning
confidence: 99%
“…Seaweeds increase the quality and performance of plants by containing cytokinins that plants need [32]. Mohammed et al [33], in their study on lettuce, reported that the number of leaves and leaf area decreased depending on the dose increase of SW applications, had no effect on stem diameter and chlorophyll content, however increased head weight and yield. Demir et al [34] observed that SW extracts were effective in seedling growth and accelerated growth.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the 'b' scale discerns between yellow and blue, with a positive value denoting yellow and a negative value denoting blue. Although a slight enhancing effect of biofertilizers on the SPAD-chlorophyll content was observed, no significant difference was found among the applications [8]. Gupta et al [59] utilized the beneficial fungus Talaromyces strain as a biostimulant for lettuce growth, and they reported an increase in photosynthetic pigments.…”
Section: Effects Of Biofertilizers On Leaf Color Propertiesmentioning
confidence: 99%
“…Agriculture is the largest sector that consumes water globally, accounting for approximately 70% of the total water demand [6,7]. Implementing an integrated irrigation and fertilization program is essential to achieving a maximum yield and high-quality production while adhering to an eco-friendly approach [8,9]. There is a growing interest in innovative farming practices characterized by a high water use efficiency and a high yield per unit area, driven by novel plant nutrition techniques.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations